2007
DOI: 10.1016/j.acn.2007.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acculturation on tests of attention and information processing in an ethnically diverse group☆

Abstract: The objective of this study was to examine differences between fluent English-speaking ethnically diverse (ED) individuals (from Hispanic, Asian and Middle-Eastern descent) and monolingual English-speaking Anglo-Americans (MEAA) on commonly used tests of information processing and attention. A sample of 123 (84 ED and 39 MEAA) healthy individuals participated. The results revealed that the MEAA group outperformed the ED group on Trail Making Test Part B, Stroop B and C, and Auditory Consonant Trigrams (18s del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 16 publications
8
76
1
Order By: Relevance
“…Currently, only a number of countries have generated normative studies for the Stroop Test within the pediatric population, including but not limited to Brazil (Oliveira et al, 2016), China (Lee, Yuen, & Chan, 2002), Italy (Barbarotto et al, 1998), México (Armengol, 2002), Portugal (Martins et al, 2005) and the U.S. (Moran & Yates, 2011). Regarding the availability of the Stroop Test and normative data for use with Latin American and Spanish pediatric populations, the majorities of the instruments used are adaptations of North American tests and standardized with American norms (Ferraro, 2015;Razani, Burciaga, Madore, & Wong, 2007). This situation has tremendous impact on the growing field of neuropsychology, especially when one considers the heterogeneity of the Latin American and Spanish population with regard to culture and education.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only a number of countries have generated normative studies for the Stroop Test within the pediatric population, including but not limited to Brazil (Oliveira et al, 2016), China (Lee, Yuen, & Chan, 2002), Italy (Barbarotto et al, 1998), México (Armengol, 2002), Portugal (Martins et al, 2005) and the U.S. (Moran & Yates, 2011). Regarding the availability of the Stroop Test and normative data for use with Latin American and Spanish pediatric populations, the majorities of the instruments used are adaptations of North American tests and standardized with American norms (Ferraro, 2015;Razani, Burciaga, Madore, & Wong, 2007). This situation has tremendous impact on the growing field of neuropsychology, especially when one considers the heterogeneity of the Latin American and Spanish population with regard to culture and education.…”
Section: Introductionmentioning
confidence: 99%
“…A series of ongoing studies have shown that the cognitive processes required for completing neuropsychological tests are dependent on cultural experience. Some aspects of culture, including the relevance of certain cognitive abilities for daily activities, may affect how well individuals acquire the skills needed to perform these tests, even among healthy samples (Razani, Burciaga, Madore, & Wong, 2007). More specifically, the demands of each culture, reflected in the daily activities of a given society, result in different ways of conceptually processing information and may increase the acquisition of specific cognitive skills and processing strategies to the detriment of others.…”
Section: Brazilians Americansmentioning
confidence: 99%
“…Americans, as a group, can be posited to have better DM skills because of more daily demands on related cognitive processes, especially those that involve economic issues. Some authors have suggested in cross-cultural studies that better scores are usually obtained by the population in which the instrument was developed because it reflects the test developer's culture and own way of perceiving the world (Razani et al, 2007).…”
Section: Brazilians Americansmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers found that white origin had better cognitive performances, especially involving verbal skills, when compared with persons of African, Hispanic, and Asian descent. However, when acculturation (i.e., age at which conversational English was first learned) was considered, they found no differences in cognitive skills across ethnic groups (Boone et al 2007;Fortuny et al 1998;Gonzales and Roll 1985;Razani et al 2007). In cognitive interviews, unacculturated research participants were reported to have more difficulties than the general public in performing cognitive skills.…”
Section: Factor To Affect Cognitive Performance: Age Education and mentioning
confidence: 94%